Development of Eighth Grade Students’ Epistemological Beliefs through Writing-to-Learn Activities - Şengül Atasoy; Osman Küçük (Universitas Pendidikan Indonesia, 2020)
The aim of the present study was to develop the epistemological beliefs of eighth grade students through writing-to-learn (WTL) activities. A one-group pretest-posttest quasi-experimental research design was utilized in the study. The sample group consisted of a total of 18 eighth grade students, attending a secondary school in the rural part of Trabzon in Turkey. To improve the epistemological beliefs of students, WTL activities were developed and utilized in the